RESPONDING TO WOMEN’S TRAVELLING WITHOUT A MAHRAM IN THE ERA OF SOCIAL TRANSFORMATION: An Analysis of Mukhtalif al-Hadith - Wulandari, Susi (RIWAYAH, 2022)
This study views two hadiths about women travelling with a mahram which at first glance seem contradictory. One hadith says that it is not lawful for women to travel without a mahram, while in another hadith, the Prophet states that there will be women who travel alone and are not afraid of anything except Allah. These two hadiths need to be studied further. The concept of mahram must be clearly understood so that there is no discrediting of women in doing something in the public sphere because many factors have encouraged women to travel in the current era of social transformation, for example, to pursue an education that necessitates being far away from family. This study uses the al-jam’u method so that these two mukhtalif hadiths about women travelling with a mahram could be applied to modern society that has undergone a social transformation. The hadith about women travelling with mahrams is substantially a concern for security on women’s travels. Suppose on the way; a woman is worried that it will be unsafe. In that case, she can practice the hadith that is not lawful for a woman’s trip if a mahram does not accompany her. In contrast, if the woman can travel safely, she can practice the second hadith about a woman travelling alone without a mahram, and there is no fear except for Allah. For this reason, modern society with social transformation can choose between the two hadiths that conform to the situation and conditions.[Permasalahan yang diangkat dalam penelitian ini tentang perempuan bepergian bersama mahram, didalam hadis-hadis yang sekilas tampak bertentangan. Salah satu hadis berisi tentang tidak halal perjalan perempuan tanpa mahram, sedangkan hadis lainnya Rasul bersabda akan ada perempuan yang bepergian sendirian dan tidak takut kepada apapun kecuali kepada Allah. Hadis-hadis tersebut perlu diketahui penyelesaiannya, serta konsep mahram perlu diketahui lebih jauh, agar tidak ada pendeskreditan terhadap perempuan didalam melakukan sesuatu di ruang public, karena banyaknya faktor yang mendorong perempuan melakukan perjalanan di era transformasi sosial saat ini, misalnya untuk mengenyam pendidikan yang mengharuskan jauh dari keluarga. Penyelesaian mukhtalif al-hadis tentang perempuan bepergian dengan mahram menggunakan metode al-jam’u, sehingga penulisan ini memiliki tujuan ialah kedua hadis mukhtalif tentang perempuan bepergian dengan mahram, dapat diaplikasikan dalam konteks masyarakat modern yang telah mengalami transformasi sosial. Hadis tentang perempuan bepergian bersama mahram secara substansi merupakan perhatian keamanan pada perjalanan perempuan. Apabila dalam perjalanannya perempuan dikhawatirkan tidak aman maka dapat mengamalkan hadis tidak halal perjalanan perempuan jika tidak disertai mahram, sedangkan jika perempuan dalam perjalanannya aman, maka dapat mengamalkan hadis tentang seorang perempuan berjalan sendirian dan tidak ada rasa takut kecuali kepada Allah. Untuk itu masyarakat modern dengan transformasi sosial dapat memilih diantara hadis keduanya yang selaras dengan situasi dan kondisi yang dihadapi.]